Gambling, fast food and alcohol sponsorship in elite sport - perspectives from Australian sporting fans - Tara Boelsen-Robinson; Anne-Marie Thow; Nancy Lee; Tim Gill; Stephen Colagiuri (BMC, 2022)
Abstract Background Public health bodies in Australia remain concerned about marketing of unhealthy commodities; namely unhealthy food, alcohol and gambling products. Children are particularly susceptible to the influence of unhealthy commodity marketing. This study explored adults' perceptions of unhealthy commodities sponsorship in elite sport and policies to restrict them. Methods Four focus groups of 7-8 frequent sport spectators were recruited, including parents and non-parents, and located in inner and outer suburbs of Sydney, Australia. Results were analysed thematically. Results Participants identified the contradictions of healthy messages of sport and unhealthy commodities, while highlighting the commercial value of sport sponsorship to sporting clubs. There is concern around children's exposure to effective and integrated marketing techniques when viewing sport, which encouraged unhealthy habits. Support for restricting sponsorship related to perceived product harm, with gambling viewed as having the greatest health impact. Participants were supportive of policies that reduced exposure of unhealthy commodities to children, but were concerned about the financial risk to sporting clubs. Governments and sports associations were identified as holding responsibility for enacting changes. Conclusion A number of options were identified for advocates to gain public and political traction to reduce unhealthy commodity sponsorship. There is potential for shifts away from unhealthy sponsorship by both governments and sports associations.